PENGARUH GAYA BELAJAR MAHASISWA TERHADAP HASIL BELAJAR PADA MATAKULIAH TEORI EKONOMI MIKRO JURUSAN PIPS UIN MAULANA MALIK IBRAHUM MALANG - Pusposari, Luthfiya Fathi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
Microeconomic theory course is compulsory subjects that must be taken a student of Social Sciences Education in UIN Maulana Malik Ibrahim Malang. Field conditions, it was found that students who prefer other subjects contained in Social Sciences such as sociology, geography and history than economic subjects, it is condition makes the results need to be improved. Many factors determine the learning outcomes of students, one of which is a learning style that is used. The purpose of this study is describe the influence of learning styles on student learning outcomes at the course of microeconomic theory in PIPS UIN Maulana Malik Ibrahim Malang, while the type of research is quantitative research with data analysis using multiple linear regression. The results showed the influence of the learning styles of students in the course of microeconomic theory to the learning outcomes, partially and simultaneously there is a positive effect but not significant, so the study received Ho. This is possible because the students know learning style but is not accompanied by quantity and the quality of learning, and the views from there are as many models of determination values above 75% are influenced by other variables.Â Keywords: learning styles, microeconomic theory and learning outcomes